Association between smoking status and outcomes in myocardial infarction patients undergoing percutaneous coronary intervention - Ching-Hui Sia (Nature Portfolio, 2021)
Abstract Smoking is one of the leading risk factors for cardiovascular diseases, including ischemic heart disease and hypertension. However, in acute myocardial infarction (AMI) patients, smoking has been associated with better clinical outcomes, a phenomenon termed the “smoker’s paradox.” Given the known detrimental effects of smoking on the cardiovascular system, it has been proposed that the beneficial effect of smoking on outcomes is due to age differences between smokers and non-smokers and is therefore a smoker’s pseudoparadox. The aim of this study was to evaluate the association between smoking status and clinical outcomes in ST-segment elevation (STEMI) and non-STEMI (NSTEMI) patients treated by percutaneous coronary intervention (PCI), using a national multi-ethnic Asian registry. In unadjusted analyses, current smokers had better clinical outcomes following STEMI and NSTEMI. However, after adjusting for age, the protective effect of smoking was lost, confirming a smoker’s pseudoparadox. Interestingly, although current smokers had increased risk for recurrent MI within 1 year after PCI in both STEMI and NSTEMI patients, there was no increase in mortality. In summary, we confirm the existence of a smoker’s pseudoparadox in a multi-ethnic Asian cohort of STEMI and NSTEMI patients and report increased risk of recurrent MI, but not mortality, in smokers.